Effect of Carboxymethyl Cellulose on the Properties of Ordinary Portland Cement - Farooque, KN; Yeasmin, Z; Halim, ME; Mahmood, AJ; Mollah, MYA (Bangladesh Journal of Scientific and Industrial Research, 2010)
Organic Polymer carboxymethyl cellulose (CMC) (0.25, 0.50 and 1.5% solution) was incorporated in Ordinary Portland Cement (OPC) and its effect on compressive strength, setting time, porosity, corrosive resistance, density and water absorbance have been studied. Organic polymer retards the setting time and a small increase in compressive strength was observed after 90 days for 0.5% CMC. Addition of polymer has been found to be effective in improving the acid resistance of OPC. Interaction of CMC with OPC causes decrease in water absorption, porosity and chemically bound water. X-ray diffraction of OPC-CMC pastes after 4 months and 1 year display some new peaks as well as disappearance of few peaks showing interaction of CMC with hydrated cementitious pastes. Examination of microstructure reveals that fibre types of matters were formed in hardened cement paste. Key words: Ordinary portland cement; Carboxymethyl cellulose (CMC); Compresssive strength; Porosity; XRD; SEM. DOI: 10.3329/bjsir.v45i1.5171 Bangladesh J. Sci. Ind. Res. 45(1), 1-8, 2010